1996
DOI: 10.1111/j.1348-0421.1996.tb01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Vulnibactin and Exocellular Protease in Utilization of Transferrin‐ and Lactoferrin‐Bound Iron by Vibrio vulnificus

Abstract: In vitro growth experiments were conducted to evaluate the ability of vulnibactin, a siderophore produced by Vibrio vulnificus, to sequester transferrin-or lactoferrin-bound iron for growth. Comparative studies with the strain producing vulnibactin and its exocellular protease-deficient mutant revealed the involvement of the protease in addition to vulnibactin in effective utilization of iron ion (Feal bound to transferrin and lactoferrin. It appears that the protease causes cleavage of these proteins, thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 28 publications
2
55
0
1
Order By: Relevance
“…Although it is essential for iron-assimilation, vulnibactin can remove iron only from transferrin digested by VVP [32]. The present study, in which VVP production was observed even at early growth phase, may support our previous conclusion.…”
supporting
confidence: 82%
“…Although it is essential for iron-assimilation, vulnibactin can remove iron only from transferrin digested by VVP [32]. The present study, in which VVP production was observed even at early growth phase, may support our previous conclusion.…”
supporting
confidence: 82%
“…15,16) However, in this study, purified VvpE was exogenously added to a culture medium in order to induce the proteolytic cleavage of transferrin or lactoferrin at culture initiation, which does not accurately simulate VvpE production during batch culture. In our previous study, 20) we argued that VvpE plays a role in iron-uptake from HT.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Of the various biological activities of VvpE, its role in facilitating V. vulnificus iron-uptake via the proteolytic cleavage of heme proteins, transferrins, and lactoferrins has attracted some attention. 15,16) However, our previous study demonstrated that an insertional mutation of vvpE gene has no direct effect on iron-assimilation from human transferrins. 20) Bacterial iron-uptake systems are themselves virulence factors in many bacterial pathogens, and are promising vaccine targets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…V. vulnificus produces both hydroxamate-and phenolate-type siderophores (17). Mutants with impaired catechol (phenolate) siderophore production are less virulent when compared with wild type V. vulnificus (11), and vulnibactin is essential for utilization of transferrin-and lactoferrin-bound iron in vivo (18). Ferric uptake regulator (Fur) 2 is the major iron-responsive transcriptional regulator in Gram-negative bacteria (19).…”
mentioning
confidence: 99%